Single-phase T-type inverter performance benchmark using Si IGBTs, SiC MOSFETs and GaN HEMTs - Gurpinar, Emre; Castellazzi, Alberto (IEEE, 2016)
In this paper, benchmark of Si IGBT, SiC MOSFET and GaN HEMT power switches at 600V class is conducted in single-phase T-type inverter. Gate driver requirements, switching performance, inverter efficiency performance, heat sink volume, output filter volume and dead-time effect for each technology is evaluated. Gate driver study shows that GaN has the lowest gate driver losses above 100kHz and below 100kHz, SiC has lowest gate losses. GaN has the best switching performance among three technologies that allows high efficiency at high frequency applications. GaN based inverter operated at 160kHz switching frequency with 97.3% efficiency at 2.5kW output power. Performance of three device technologies at different temperature, switching frequency and load conditions shows that heat sink volume of the converter can be reduced by 2.5 times by switching from Si to GaN solution at 60°C case temperature, and for SiC and GaN, heat sink volume can be reduced by 2.36 and 4.92 times respectively by increasing heat sink temperature to 100°C. Output filter volume can be reduced by 43% with 24W, 26W and 61W increase in device power loss for GaN, SiC and Si based converters respectively. WBG devices allow reduction of harmonic distortion at output current from 3.5% to 1.5% at 100kHz.